Fungal network composition and stability in two soils impacted by trifluralin - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Xu, Huifang; Zheng, Xiaoke; Zhang, Changpeng; Du, Pengqiang (Frontiers in Microbiology, 2023)
Introduction The composition and stability of soil fungal network are important for soil function, but the effect of trifluralin on network complexity and stability is not well understood. Methods In this study, two agricultural soils were used to test the impact of trifluralin on a fungal network. The two soils were treated with trifluralin (0, 0.84, 8.4, and 84 mg kg−1) and kept in artificial weather boxes. Results and discussion Under the impact of trifluralin, the fungal network nodes, edges, and average degrees were increased by 6–45, 134–392, and 0.169–1.468 in the two soils, respectively; however, the average path length was decreased by 0.304–0.70 in both soils. The keystone nodes were also changed in trifluralin treatments in the two soils. In the two soils, trifluralin treatments shared 219–285 nodes and 16–27 links with control treatments, and the network dissimilarity was 0.98–0.99. These results indicated that fungal network composition was significantly influenced. After trifluralin treatment, fungal network stability was increased. Specifically, the network robustness was increased by trifluralin with 0.002–0.009, and vulnerability was decreased by trifluralin with 0.0001–0.00032 in the two soils. Fungal network community functions were also impacted by trifluralin in both soils. Trifluralin significantly impacts the fungal network.